2020
DOI: 10.1016/j.cgh.2019.11.059
|View full text |Cite
|
Sign up to set email alerts
|

Ustekinumab Pharmacokinetics and Exposure Response in a Phase 3 Randomized Trial of Patients With Ulcerative Colitis

Abstract: BACKGROUND & AIMS:The efficacy of antibody-based therapeutics depends on their pharmacokinetics. The pharmacokinetic and exposure response profiles of ustekinumab, a monoclonal antibody against interleukin 12/interleukin 23, are known in patients with Crohn's disease, yet there are few data from patients with ulcerative colitis. We characterized ustekinumab's pharmacokinetics, exposure response, and optimal serum concentrations in patients with ulcerative colitis. METHODS:We collected data from 2 phase 3 trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 34 publications
3
60
2
Order By: Relevance
“…While for patients treated with tumour necrosis factor (TNF)‐alpha inhibitors, therapeutic drug monitoring may provide important guidance for selection of strategy 23‐26 . The correlation of ustekinumab levels with treatment outcomes is not as robust 6,12,27 . Thus, the escalation strategy is currently empiric and nonstandardised.…”
Section: Discussionmentioning
confidence: 99%
“…While for patients treated with tumour necrosis factor (TNF)‐alpha inhibitors, therapeutic drug monitoring may provide important guidance for selection of strategy 23‐26 . The correlation of ustekinumab levels with treatment outcomes is not as robust 6,12,27 . Thus, the escalation strategy is currently empiric and nonstandardised.…”
Section: Discussionmentioning
confidence: 99%
“…Also, all the prospective studies available to date have shown no impact of immunomodulator on the trough serum level of vedolizumab 35,55 or ustekinumab. 9,56 The association of immunomodulators with biologics may also be deleterious. Combination with anti-TNF is associated with an increased risk of serious, opportunistic infections and lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, these drugs are less immunogenic, and it is not certain that adding an immunomodulator improves their efficacy. 5,6,[9][10][11] On the other hand, the addition of an immunomodulator may be deleterious because of increased risk of serious and opportunistic infections. 12,13 Hence, we aimed to evaluate the comparative effectiveness and safety of using vedolizumab or ustekinumab monotherapy vs in combination with an immunomodulator in patients with IBD through a systematic review and meta-analysis.…”
mentioning
confidence: 99%
“…Interestingly, in a retrospective analysis of IBD patients on maintenance therapy with vedolizumab, TLs <7.4 μg/mL, in patients experiencing LOR was associated with a significantly increased likelihood to respond to dose escalation compared to higher concentrations (OR 3.7, 95% CI 1.1-13, p = 0.04) [108]. A similar exposure-efficacy relationship has been observed for ustekinumab: early TLs (week 4 and 8) have been associated with clinical remission [109,110], decrease of faecal calprotectin [111] and biochemical remission [112], while TLs during maintenance have been correlated with clinical remission [109,110], endoscopic response [111,113] and need for optimization [114]. In a recent review, Alsoud et al [127] proposed target TLs for vedolizumab and ustekinumab.…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 68%